Evaluasi Proposal Program Kreativitas Mahasiswa (PKM) Menggunakan Sistem WP - Risnawati; Pasrun, Yuwanda Purnamasari; Iin, Johar Nur; Muchtar, Mutmainnah (Fakultas Teknologi Informasi, 2024)
The evaluation procedure for Student Creativity Program (PKM) projects necessitates an objective and efficient methodology to analyze several aspects. This project seeks to establish an evaluation system utilizing the Weighted Product (WP) approach to deliver transparent and quantifiable rankings of proposals. The review utilized five primary criteria: thematic relevance, innovation and creativity, technological feasibility, potential impact, and program sustainability, each assigned predetermined weights. Data from ten proposals were evaluated utilizing the WP approach, encompassing the phases of decision matrix normalization, preference value computation, and ranking. The findings indicated that Proposal 4 garnered the highest preference value (4.939), succeeded by Proposal 5 (4.889) and Proposal 2 (4.876), establishing them as the foremost recommendations for funding. The WP technique shown efficacy in improving the efficiency and impartiality of the PKM proposal selection process. This method's implementation can be utilized in other programs with comparable assessment difficulties